ANALISIS KINERJA PENGOLAHAN SAMPAH DI KOTA METRO (STUDI DI TEMPAT PENGOLAHAN AKHIR SAMPAH (TPAS) KOTA METRO (Jurusan Ilmu Administrasi Publik, Universitas Lampung, 2018)
The purpose of this study are analysis of the performance of Waste in Metro City Sanitation Unit, and the application of the principles of Good Governance in UPT Cleanliness Metro City. The results showed Performance Of sewage treatment UPT Cleanliness Metro City quite well, evidenced by the hygiene conditions of the main road, and achievement, able to earn trophies Verse, a Clean City, increasing the results of revenue (PAD) from the levy cleanliness of Metro City, although it has not been thorough City area Metro accessible because of his lack of the number of worker / clerk pengakut garbage and facilities are inadequate, for the adoption of the principles of Good Governance, UPT Cleanliness Metro apply the principle of participation that the increased awareness and public confidence in the UPT Cleanliness Metro City with the volume of waste generated Metro city is quite high, it terihat of incoming data to Landfill Waste (TPAS) in Karangrejo Metro Tinur reached 210-225 cubic, public participation in the separation of household waste organic and inorganic, and physical activity / work devotion.